Paper microfluidic device using carbon dots to detect glucose and lactate in saliva samples - Rossini, Eduardo Luiz [UNESP]; Milani, Maria Izabel [UNESP]; Lima, Liliane Spazzapam [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2021)
Bioanalyses are commonly performed with blood or serum samples. However, these analyses often require invasive and painful blood collection using a needle or finger pricking. Saliva is an alternative and very attractive biological medium for performing clinical analyses, since it contains many types of clinically relevant biomarkers and compounds. Its collection is straightforward and can be achieved in a non-invasive and stress-free way. However, the analytes are frequently present at low concentrations, while the viscosity of whole saliva hinders its analysis using paper devices, especially those with multiple layers (3D-μPADs). This work explores the use of a simple, fast, and low-cost saliva sample pretreatment using a cotton-paper-syringe filtration system, allowing the analysis of saliva samples using multilayer paper devices. The proposed methodology employs the oxidation of glucose and lactate, catalyzed by specific oxidase enzymes, producing hydrogen peroxide. The detection is based on the fluorescence quenching of carbon dots in the presence of hydrogen peroxidase. The concentrations of the analytes showed good linear correlations with the fluorescence quenching, with LODs of 2.60 × 10−6 and 8.14 × 10−7 mol L−1 for glucose and lactate, respectively. The proposed method presented satisfactory intra-day and inter-day repeatabilities, with %RSD values in the range 3.82–6.61%. The enzymatic systems proved to be specific for the analytes and the matrix had no significant influence on the glucose and lactate determinations. The proposed methodology was successfully applied to saliva and serum samples and was validated using certified material.
Keywords: Carbon dots; Filtration; Glucose; Lactate; Paper platform; Saliva; Serum